2007
DOI: 10.1093/annonc/mdl335
|View full text |Cite
|
Sign up to set email alerts
|

MR-guided focused ultrasound surgery (MRgFUS) for the palliation of pain in patients with bone metastases—preliminary clinical experience

Abstract: MRgFUS may provide a safe and effective noninvasive alternative for the palliation of pain, caused by bone metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
175
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(180 citation statements)
references
References 21 publications
5
175
0
Order By: Relevance
“…Prospective, single-arm multicenter trials have shown RFA and cryoablation to be safe and highly effective for treatment of symptomatic skeletal metastases [12][13][14][15][16]. A large randomized, controlled, multicenter phase III trial has shown Focused Ultrasound (FUS) to be effective in the treatment of painful bone metastases [17], confirming results of earlier retrospective reports [18]. Small case series also support benefit from other percutaneous methods of image-guided ablation, including microwave ablation, laser ablation, and irreversible electroporation to treat skeletal metastases, although the data are more limited [19][20][21][22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 57%
“…Prospective, single-arm multicenter trials have shown RFA and cryoablation to be safe and highly effective for treatment of symptomatic skeletal metastases [12][13][14][15][16]. A large randomized, controlled, multicenter phase III trial has shown Focused Ultrasound (FUS) to be effective in the treatment of painful bone metastases [17], confirming results of earlier retrospective reports [18]. Small case series also support benefit from other percutaneous methods of image-guided ablation, including microwave ablation, laser ablation, and irreversible electroporation to treat skeletal metastases, although the data are more limited [19][20][21][22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 57%
“…Cortical bone is characterized by a high absorption of ultrasound and low thermal conductivity. This is an advantage in the treatment of painful bone metastases, since the maximum energy deposition occurs in the region of periosteal localized pain fibers [11]. On the whole, the procedure is quite time-consuming since the resulting ablation area is relatively small (between 50 and 300 mm 3 ).…”
Section: High-intensity Focused Ultrasound (Hifu)mentioning
confidence: 99%
“…In the case of the brain, when the skull surrounds the target the penetration of acoustic energy through the bone can cause such heating, a seemingly irresolvable problem. This effective heating of bone with FUS can be used to one's advantage with the palliative treatment of painful bone metastases (24).…”
Section: Thermal Ablation With Mrgfus: New Clinical Applicationsmentioning
confidence: 99%
“…While large studies have not yet been performed, initial results of MRgFUS treatment of bone metastases have been extremely promising (24) and potentially offer relatively fast and significant pain reduction. Figure 3 shows an example of MR thermometry during one of these treatments.…”
Section: Bonementioning
confidence: 99%
See 1 more Smart Citation